Who Owns Our Ancestors’ Voices? - Reed, Trevor (The Columbia Journal of Law & the Arts, 2017)
In Part I, this Note will explore federal cultural property statutes as well as the doctrines of common law copyright and aboriginal title, each of which might be employed to determine ownership interests in pre-1972 sound recordings made on Indian reservations. In Part II, this Note will present a case study, involving a nonindigenous collector who captured a massive body of Native American cultural expression prior to 1972, to illustrate the complexities of applying cultural property statutes and common law doctrines to these types of materials in the present. Finally, recognizing that the Copyright Act’s treatment of pre-1972 sound recordings has been identified by Congress as an area in need of revision,1 Part III explores the potential risks and benefits of applying the Copyright Act’s frameworks to pre-1972 sound recordings made on federally recognized Indian reservations. If Congress does have the power to impose these frameworks on pre- 1972 sound recordings made on tribal lands, how might such a framework affect tribal communities? And, should tribal communities oppose such a move by Congress?